2008
DOI: 10.1021/ja806304s
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Asymmetric Total Synthesis of (−)-Laurefucin via an Organoselenium-Mediated Intramolecular Hydroxyetherification

Abstract: The first asymmetric total synthesis of (-)-laurefucin (1), a unique C-15 acetogenin with a 2,8-dioxabicyclo[5.2.1]decane skeleton, has been accomplished in nine steps in 31% overall yield from known oxocene 10. Highlights of the highly stereoselective synthesis include a novel organoselenium-mediated biomimetic hydroxyetherification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 42 publications
2
45
0
Order By: Relevance
“…However, the stereochemical outcome of epoxidation of ,'-trans-,-unsaturated oxocene alcohol 7 caused some concern owing to the known conformational preferences,'-trans-oxocenes (vide infra). As a second approach, we were particularly intrigued by the possibility that a novel organoselenium-mediated alkoxyetherification of 7 in MeOH, which involves a selenoetherification/activation/oxonium ion formation/fragmentation sequence [7  10  9  8  4] as depicted in the scheme, 9 might provide a direct access to the dioxabicyclic core of isolaurefucin methyl ether 2. In the earlier mentioned recent synthesis of halofucins, we reported that key intermediate 7 could be synthesized from readily available (R)-1-penten-3-ol via an efficient nine-step sequence in 46% overall yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the stereochemical outcome of epoxidation of ,'-trans-,-unsaturated oxocene alcohol 7 caused some concern owing to the known conformational preferences,'-trans-oxocenes (vide infra). As a second approach, we were particularly intrigued by the possibility that a novel organoselenium-mediated alkoxyetherification of 7 in MeOH, which involves a selenoetherification/activation/oxonium ion formation/fragmentation sequence [7  10  9  8  4] as depicted in the scheme, 9 might provide a direct access to the dioxabicyclic core of isolaurefucin methyl ether 2. In the earlier mentioned recent synthesis of halofucins, we reported that key intermediate 7 could be synthesized from readily available (R)-1-penten-3-ol via an efficient nine-step sequence in 46% overall yield.…”
Section: Resultsmentioning
confidence: 99%
“…Even though we were able to construct the isolaurefucin skeleton via the intramolecular epoxide opening route with decent stereoselectivity (3.6:1), we still wished to explore the direct synthesis of isolaurefucin methyl ether surrogate 4 via the projected novel organoselenium-mediated intramolecular alkoxyetherification of ,'-trans-,-unsaturated oxocene alcohol 7 in MeOH. In our synthesis of laurefucin (1), 9 we reported that exposure of ,'-cis-,-unsaturated oxocene alcohol 7' to excess N-phenylselenophthalimide (N-PSP) 18 In an experiment parallel to that of ,'-cis-,-unsaturated oxocene alcohol 7', subjection of ,'-trans-,-unsaturated alcohol 7 to the abovementioned comparable hydroxyetherification conditions gave rise to a 1:1 mixture (96% total yield) of the desired hydroxyl-ether 5 with an ,'-trans-2,8-dioxabicyclo[5.2.1]decane skeleton and bis-tetrahydrofuranyl alcohol 12. This latter presumably arises from attack at the C7 position of oxonium ion 8, and we were somewhat surprised that it was produced in such abundance.…”
Section: Scheme 3 Epoxidation and Intramolecular Epoxide Openingmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy-minimized conformations were optimized by the density functional theory method (PBE) at the DND level (DMol 3 ) (Kim et al, 2008). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our successful efforts along these lines are exemplified in our synthesis of elemol (29), as summarized in Scheme 10. 16 In this work, we established the relative stereochemistry of all three stereogenic centers in the natural product in a single operation using a folding strain controlled intramolecular S N 2′ ester enolate alkylation (30 → 31), which probably proceeds through chairlike double Heclipsed transition state geometry C, as depicted in Scheme 10.…”
Section: Intramolecular S N 2′ Enolate Alkylationmentioning
confidence: 99%